Perioperative and oncological outcomes of abdominoperineal resection in the prone position vs the classic lithotomy position: A systematic review with meta‐analysis. Issue 7 (6th February 2019) - Mesquita‐Neto, Jose Wilson B.; Mouzaihem, Hassan; Macedo, Francisco Igor B.; Heilbrun, Lance K.; Weaver, Donald W.; Kim, Steve
Abstract: Background and Objectives: This study is a systematic review with meta‐analysis designed to compare the perioperative and oncological outcomes of the abdominoperineal resection (APR) carried out in the prone jack‐knife position (P‐APR) vs the classic lithotomy position (C‐APR). Methods: We conducted an electronic search through PubMed utilizing the PRISMA guidelines. We included all randomized and nonrandomized studies which allowed for comparative analysis between the two groups. Research that focused on and analyzed the extralevator abdominal excision were excluded. Pooled variables and number of events were analyzed using the random‐effect model. Results: The final analysis included seven nonrandomized retrospective cohorts encompassing 1663 patients. P‐APR was associated with decreased operative time (OT) (DM, −43.8 minutes; P  < 0.01) and estimated blood loss (EBL) (DM, 86.9 mL; P  < 0.01). There were no observed differences regarding perineal wound infections (PWI) (odds ratio [OR], 0.36; P  = 0.18), intraoperative perforation of rectum (IOP) (OR, 0.98; P  = 0.97), circumferential resection margin (CRM) positivity (OR, 1.02; P  = 0.98) or 5‐year LR (OR, 1.00; P  = 0.99). Conclusion: The prone approach for APR is associated with decreased EBL and OT, although not with any change in the incidence of PWI or IOP. Moreover, surgical positioning per se does not appear to affect the CRM positivity rates or LR rate.